REGULAMENTAÇÃO DOS SISTEMAS DE INTELIGÊNCIA ARTIFICIAL NO ORDENAMENTO JURÍDICO BRASILEIRO (REMUNOM, 2024)
AbstractThe present article aims to address the regulation of artificial intelligence (AI) systems in the Brazilian legal context. Initially, it explores the emergence and evolution of AI, highlighting its impact on global transformations and its growing role in contemporary society. With technological advancement, the demand for autonomous agents capable of innovatively addressing challenges has increased, driving the integration of AI with Big Data and other technologies. In the legal sphere, the application of AI has enabled the adoption of strategies such as predictive policing and automated decision systems. However, ethical and legal questions arise regarding the legal nature of AI, whether they should be considered mere objects of law or subjects of law with their own legal personality. Additionally, the civil liability of AI in cases of harm to jurisdictional entities is discussed. To achieve these objectives, the article proposes a methodology based on exploratory, descriptive, and deductive bibliographic research, using legislation, doctrine, jurisprudence, and scientific articles as sources for analysis. This study contributes to the debate on AI regulation, aiming to ensure the protection of individual rights, appropriate accountability, and the promotion of justice in the field of civil law.Keywords: artificial intelligence; jurisdiction; legal system; civil liability